Warm Terrestrial Subtropics During the Paleocene and Eocene: Carbonate Clumped Isotope (Δ47) Evidence From the Tornillo Basin, Texas (USA). Issue 11 (9th November 2018) - Kelson, Julia R.; Watford, Dylana; Bataille, Clement; Huntington, Katharine W.; Hyland, Ethan; Bowen, Gabriel J.
Abstract: Records of subtropical climate on land from the early Paleogene offer insights into how the Earth system responds to greenhouse climate conditions. Fluvial and floodplain deposits of the Tornillo Basin (Big Bend National Park, Texas, USA) preserve a record of environmental and climatic change of the Paleocene and the early Eocene. We report carbon, oxygen, and clumped isotopic compositions (δ 13 C, δ 18 O, and Δ47 ) of paleosol carbonate nodules from this basin. Mineralogical, geochemical, and thermal modeling evidence suggests that the measured isotopic values preserve primary environmental signals with a summer bias with the exception of data from two nodules reset by local igneous intrusions. The unaltered nodules record Δ47 temperatures of 25 ± 4 and 32 ± 2 °C for the Paleocene and early Eocene nodules, respectively, showing an increase in average summer temperatures of 7 ± 3 °C. Calculations of δ 18 O of soil water are −2.8 ± 0.7‰ and −0.8 ± 0.4‰ (standard mean ocean water) for the early‐mid‐Paleocene and late Paleocene‐early Eocene, showing an increase of 2.0 ± 0.9‰. The increase in temperature and δ 18 O values likely relates to a rise in atmospheric p CO2, although we cannot rule out that changes in paleosol texture and regional precipitation patterns also influence the record. Comparison with Δ47 estimates of summer temperature from the Green River and Bighorn Basins (WY) highlights that terrestrial surface temperatures are heterogeneous, and latitudinal temperature gradients on land remain undetermined. Previously published paleoclimate models predict summer temperatures that are 2 to 6 °C higher than our estimate; discrepancies between climate models and proxy data persist at lower latitudes. Key Points: Paleosol carbonate nodules from the Tornillo Basin record primary environmental values of carbon, oxygen, and clumped isotopes Carbonate nodules record average clumped isotope temperatures of 25 ± 4 and 32 ± 2 °C for the Paleocene and early Eocene, respectively These temperature estimates are lower than model predictions, and data‐model discrepancies remain at low latitudes for the Eocene